Considerations for anesthesia staffing in a trauma center. Issue 2 (April 2015) - Banks, Shawn E.; Sharp, Christopher; Fouche, Yvette L.; Haycock, Jo; Dagal, Armagan
<x xml:space="preserve">Abstract</x> Purpose of review A review of recent updates to trauma anesthesia service requirements in the USA and UK, the evolving role of the trauma anesthesiologist, and opportunities for education and training. Considerations of cost and safety for staffing arrangements are discussed. Recent findings Certifying and specialty organizations have recently escalated the availability requirements and training recommendations for anesthesiology services in trauma centers. Summary There is a growing recognition that trauma anesthesiology represents a distinct area of subspecialty knowledge. Anesthesiology specialty organizations advocate for trauma-specific knowledge and training for trauma anesthesia providers. Requiring the in-house presence of anesthesia providers in level I and level II trauma centers may impose significant costs on medical centers that do not currently provide those services.